Characterization of Polyvinylpyrrolidone-2-Acrylamide-2-Methlypropansulphonic Acid Based Polymer as a Corrosion Inhibitor for Copper and Brass in Hydrochloric Acid - Makhatha, Mamookho Elizabeth; Tsoeunyane , George M.; Yvette Maqubela, Luyanda Masana; Sherbakov, Sergei; Podgayskaya, Daria; H. M., Vishwanatha; Kumar, Pawan (Applied Science and Engineering Progress, 2025)
Copper and its alloy are susceptible to corrosion in heat exchangers during acid cleaning. The corrosion leads to materials loss and damage; hence it is important to prohibit such corrosion damage using an eco-friendly corrosion inhibitor. In the current work, a polymer composite-based corrosion inhibitor was prepared using polyvinylpyrrolidone (PVP) and 2-Acrylamido-2-methylpropane sulfonic acid (AMPS). The PVP copolymer undergoes polymerization with the AMPS having several interconnected uniformly sized pores and produces a PVP–AMPS composite with rod-like microstructure. The effect of concentration, time, and temperature on corrosion inhibition efficiency (IE) of PVP–AMPS composite was studied for copper and brass in hydrochloric acid (HCl) solution. The IE increases with concentration and decreases with time and temperature. A change in cathodic and anodic Tafel slopes with the concentration of PVP–AMPS inhibitors was observed. The increase in IE with concentration was attributed to the solubility of PVP–AMPS composite in HCl. However, the decrease in IR with time and temperature was due to the desorption of PVP–AMPS composite from the surface of copper and brass and also due to the exothermic reactions at higher temperature. A few peaks in FTIR spectra at 3000–3100 cm−1 were missing, which is due to the stretching vibration of H–C during the crosslinking polymerization. Further, the absence of the O–H peak indicated that the polymerization process removed the water molecule. The best correlation coefficient (R2) for the Langmuir adsorption mechanism was achieved. A negative Gibbs free energy (ΔG) envisages the spontaneity of the adsorption process. However, the | ΔG| for adsorption was less than 20 kJmol−1 confirming the process as physisorption. A shift in anodic and cathodic branches in the presence of the PVP–AMPS inhibitor indicated a mixed-type inhibitor behavior.